2021
DOI: 10.3390/w13172397
|View full text |Cite
|
Sign up to set email alerts
|

The Stable Isotope Characteristics of Precipitation in the Middle East Highlighting the Link between the Köppen Climate Classifications and the δ18O and δ2H Values of Precipitation

Abstract: The Middle East is faced with a water shortage crisis due to its semiarid and arid climate. In this paper, precipitation as an important part of the water cycle was evaluated in 43 stations across the Middle East using the stable isotope technique to study the parameters which influence the stable isotope content of precipitation. First, the stepwise regression model was applied to determine the main geographical and climatological factors affecting the stable isotopes in precipitation. Secondly, the stepwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
0
0
Order By: Relevance
“…The high isotope composition (δ 2 H and δ 18 O) in precipitation of the study area gives good agreement with the high values observed in eastern tropical Africa and the Arabian Peninsula in previous studies (Leng 2006;Michelsen et al 2015;Heydarizad et al 2021). This indicates the climate conditions in these regions have a great influence on stable isotopes values in precipitation.…”
Section: Discussionsupporting
confidence: 90%
“…The high isotope composition (δ 2 H and δ 18 O) in precipitation of the study area gives good agreement with the high values observed in eastern tropical Africa and the Arabian Peninsula in previous studies (Leng 2006;Michelsen et al 2015;Heydarizad et al 2021). This indicates the climate conditions in these regions have a great influence on stable isotopes values in precipitation.…”
Section: Discussionsupporting
confidence: 90%
“…It is the most populous metropolitan area in West Asia, and the Middle East's most populous metropolitan area (Figure 1a). The Köppen climate classification places Tehran in the BSk group with a cold se arid climate [24]. Tehran's climate is heavily influenced by the geographic features t separate the city's northern (Alborz Mountains) and southern (central desert) halv Mount Damavand located near Tehran, has the highest elevation in Iran and even Middle East region.…”
Section: The Climate and Topography Of Tehranmentioning
confidence: 99%
“…During the cold period (November to April), the monthly precipitat amount showed higher values, while the water vapour pressure and air temperat showed lower values, compared to the warm period (May to October) of the year. T The Köppen climate classification places Tehran in the BSk group with a cold semiarid climate [24]. Tehran's climate is heavily influenced by the geographic features that separate the city's northern (Alborz Mountains) and southern (central desert) halves.…”
Section: The Climate and Topography Of Tehranmentioning
confidence: 99%
See 2 more Smart Citations